Wednesday

April 23, 2014

April 23, 2014

Posted by **BERNIE** on Wednesday, August 22, 2012 at 7:59pm.

find the following pairs

a)(f 0 g)(x), b)(f 0 g)(-3) c) (g 0 f)(x) c)(g 0 f)(4)

I am haing trouble with these two, can you please help me

thankyou

- algebra 2 -
**Reiny**, Wednesday, August 22, 2012 at 10:25pmI will use the more traditional way of writing these

(f 0 g)(x)

= f(g(x))

= f(6x^2 - 3x + 6)

= 2(6x^2 - 3x + 6) or 12x^2 - 6x + 12

(f 0 g)(-3))

= 12(9) - 6(-3) + 12 = 138

or

g(-3) = 6(9) - 3(-3) + 6 = 69

f(g(-3)) = f(69) = 138

try the others the same way

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Math - Pair of functions fx=3x and g(x) =3x^2-2x+3 find the following (f◦g...

Calculus 12th grade (double check my work please) - 2- given the curve is ...

Algebra - Need help with these-- 6. Chase scored 14 points on Monday, and he ...

Calculus - Find the sum and difference functions f + g and f – g for the ...

algebra - simplify (6x^3-16x^2+11x-5)/(3x-2) (3x-2)(2x-1)^2-3 my muliple choice ...

Math - Can someone please check my answers below for accurateness? The ...

algebra - Find a trinomial A(x) that represents the area of a parallelogram ...

math - f(x)=-x^3+3x^2+9x-5 asked to find the stationary points this was my ...

algebra - 1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n...